A murine model of dengue virus infection in suckling C57BL/6 and BALB/c mice. Issue 1 (21st December 2020) - Byrne, Alana B.; García, Ayelén G.; Brahamian, Jorge M.; Mauri, Aldana; Ferretti, Adrián; Polack, Fernando P.; Talarico, Laura B.
Abstract: Dengue is a significant public health concern across tropical and subtropical regions worldwide, principally causing disease in children. Very young children are at increased risk of severe manifestations of dengue infection. The mechanism of dengue disease in this population is not fully understood. In this study, we present a murine model of dengue virus primary infection in suckling C57BL/6 and BALB/c mice in order to investigate disease pathogenesis. Three‐day‐old C57BL/6 mice intraperitoneally infected with DENV‐2 NGC were more susceptible to infection than BALB/c mice, showing increased liver enzymes, extended viremia, dissemination to organs and histological alterations in liver and small intestine. Furthermore, the immune response in DENV‐infected C57BL/6 mice exhibited a marked Th1 bias compared to BALB/c mice. These findings highlight the possibility of establishing an immunocompetent mouse model of DENV‐2 infection in suckling mice that reproduces certain signs of disease observed in humans and that could be used to further study age‐related mechanisms of dengue pathogenesis.